The oddly pedestrian life of Christopher Chaos - Brombal, Tate; Tynion, James IV 1987- (Dark Horse Books, a division of Dark Horse Comics, 2024)
"Collects The oddly pedestrian life of Christopher Chaos #1-6 and a ten-page prolouge"--Tp verso
Keywords: Teenagers -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Scientists -- Comic books, strips, etc; Wissenschaftler; Männliche Jugend -- 14-21 Jahre; Ungeheuer; Kult; Graphic novels / United States; Monster comics; Comic; Queer comics